Relationship between bone age and chronological age of football players of the province of Imbabura (Horizontes de Enfermería, 2018)
Currently the Ecuadorian Soccer Championshio maintans its activities between the Major División and the Training Divisions; without there being a correct control between the ages to which the Ecuadorian soccer players work at a profesional level. Doing repeatedly in sporting events, in lower divisions many inequalities in the physical composition of athletes are noted, which is interpreted as age inequality. And that has caused problems and sanctions at the national and international level due to the non-agreement of the ages. And that the chronological age registered in the Civil Registry is exposed to many doubts. For this reason is necessary to adequately control the chronological age and the civil age a non invasive examination is the Carpogram tha determines bone age with a minimun margin of error that will serve constantly to assess the maduration and growth of footballers.
Keywords: Carpogram; soccer; chronological; age; growth; maturation